Informated asphalt: the impact of information technology on urban traffic management - Rajão, Raoni Guerra Lucas (Revista Economia & Gestão, 2008)
This paper considers changes in the nature of traffic management brought about by the introduction of different technologies, mostly geographic information systems (GIS). Traffic management has changed significantly since it was born about a century ago. The invention of automatic traffic lights prompted the devaluation of action-centred skills needed to manage traffic. This process was further advanced with the introduction of geographic information systems and the consequent virtualization of the work environment. In order to analyze those transformations, the paper reviews Zuboff’s work (1988) twenty years after its publication. It argues that GIS have great potential not only to automate work activities but also to informate the organisation, providing a fresh view of its own reality. According toher, in order to use the information capability of GIS, the worker needs intellective skills. Besides, the organization has to provide a favourable context to explore this capability.Another consequence of the introduction of GIS is the appearance of a new form of control by surveillance: Panopticon information. Even though Zuboff’s ideas about the two faces of Information Technology and Panopticon provide an insightful framework to analyse changes in the nature of work, her assumptions about the rational use of information in the decisionmaking process may not always occur in reality. The case study at hand and research on theactual use of information in organizations contrast with Zuboff’s suggestion that IT leads to a strictly rational use of information.